Composition of the essential oils of two Teucrium species from Turkey - Hayta, Şükrü; Yazgın, Ayşe; Bağcı, Eyup (Bitlis Eren Üniversitesi, 2017)
ABSTRACT: The chemical composition of the essential oils of dried aerial parts of two Teucrium species were analyzed by GC and GC-MS. The essential oils of  two Teucrium species  were studied and eighty components, in all, were identified representing (90.8%) and (82.4%) of the oils respectively.  The oil of Teucrium polium L. subsp. polium is characterized by the monoterpene b-pinene (10.2%) and the sesquiterpene germacrene D (10.1%), while that of Teucrium multicaule Montbret Et Aucher Ex Bentham had a higher contents of sesquiterpene caryophyllene oxide (31.1%). Quantitative and qualitative variations were determined in the essential oil composition of different parts of the studied plant. The high amount of monoterpenes ?- and ?-pinene and the sesquiterpene germacrene D, caryophyllene oxide make the studied taxon a privileged potential source for pharmaceutical, cosmetic and industrial products.